Answer:
y = 5(x - 1)² - 3
Explanation:
The equation of a quadratic in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
To obtain this form use the method of completing the square
• The coefficient of the x² - term must be 1
Factor out 5 from the first 2 terms
y = 5(x² - 2x) + 2
• add/subtract (half the coefficient of the x- term)² to x² - 2x
y = 5(x² + (- 1)x + (- 1)² - (- 1)² ) + 2 ← complete the square
y = 5(x - 1)² - 5 + 2
y = 5(x - 1)² - 3 ← in vertex form